Challenges and Strategies in Translating English Collocations into Kurdish: A Linguistic Approach - Zana Hama Amin (Language, Technology, and Social Media, 2023)
This study examines the challenges faced by Kurdish EFL learners in translating English collocations and explores strategies to enhance their translation competence. Using a mixed-methods approach, the research involved 20 fourth-year students from the University of Sulaimani, who were tested on their ability to translate 16 English collocations across six structural types: noun + noun, adjective + noun, verb + noun, verb + adverb, adverb + adjective, and noun + verb. The findings reveal a significant difficulty in translation, with only 35.31% of responses being correct. Students performed best in verb + adverb (90% accuracy) and noun + verb (75% accuracy) combinations, while adjective + noun (30%) and verb + noun (12.5%) collocations posed the greatest challenges. Qualitative analysis identified three primary issues: reliance on literal translation, cultural mismatches, and structural misalignment between English and Kurdish. For example, collocations like "dry voice" and "pay a visit" were often mistranslated due to differences in cultural and syntactic norms. The study highlights the importance of explicit collocation instruction, cultural awareness training, and the development of bilingual resources to address these challenges. This study contributes novel insights into the linguistic and cultural factors affecting collocation translation and provides practical recommendations for enhancing Kurdish EFL learners' proficiency. These findings are significant for educators, linguists, and policymakers in developing curricula that prioritize collocational competence and cultural understanding in language education.